2020
DOI: 10.1039/c9tc05881h
|View full text |Cite
|
Sign up to set email alerts
|

Substrate mediated electronic and excitonic reconstruction in a MoS2 monolayer

Abstract: The atomically thickness of two-dimensional materials (2D) makes their physical and chemical properties vulnerable to external influence. In this study, we show that the electronic and optical properties of MoS2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…5, MoS 2 has a peak near 600 nm when without SOC, which is consistent with the previously reported lowest exciton jump energy of MoS 2 of around 2 eV. 52 After considering SOC, the optical bandgap becomes smaller and the first peak appears at about 1.9 eV, which corresponds to the peak larger than 600 nm in this figure. After considering SOC, the lowest excitonic state of 2D MoGe 2 P 4 is located at around 770 nm.…”
Section: Optical Absorption Propertiessupporting
confidence: 91%
“…5, MoS 2 has a peak near 600 nm when without SOC, which is consistent with the previously reported lowest exciton jump energy of MoS 2 of around 2 eV. 52 After considering SOC, the optical bandgap becomes smaller and the first peak appears at about 1.9 eV, which corresponds to the peak larger than 600 nm in this figure. After considering SOC, the lowest excitonic state of 2D MoGe 2 P 4 is located at around 770 nm.…”
Section: Optical Absorption Propertiessupporting
confidence: 91%
“…In order to obtain the improved toughness and the decreased processing temperature, a large amount of suitable plasticizer needs to be added into PLA polymer matrix. During the last decade, the production of plasticizers was around 6.4 million tons all over the world per year, it was estimated that more than 13.2 million tons per year in 2018 . Unfortunately, most plasticizers are difficult to degrade in natural environment and easy to migrate due to their high mobility within the PLA matrix .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent studies demonstrated that substrate has an important screening effect that reduces the electron−hole interaction. 74,75 Therefore, the screening from MoS 2 may also reduce the electron− hole recombination rate in the ReSe 2 /MoS 2 heterostructure.…”
mentioning
confidence: 99%
“…Furthermore, in 2D semiconductor materials, the strong exciton effect usually exists due to quantum confinement and reduced dielectric screening, and the exciton binding energy is susceptible to the external influences. For instance, recent studies demonstrated that substrate has an important screening effect that reduces the electron–hole interaction. , Therefore, the screening from MoS 2 may also reduce the electron–hole recombination rate in the ReSe 2 /MoS 2 heterostructure.…”
mentioning
confidence: 99%